Nanoparticles as a Promising Strategy to Mitigate Biotic Stress in Agriculture - Gonzalo Tortella; Olga Rubilar; Joana C. Pieretti; Paola Fincheira; Bianca de Melo Santana; Martín A. Fernández-Baldo; Adalberto Benavides-Mendoza; Amedea B. Seabra (MDPI AG, 2023)
Nanoparticles are recognized due to their particular physical and chemical properties, which are conferred due to their size, in the range of nanometers. Nanoparticles are recognized for their application in medicine, electronics, and the textile industry, among others, but also in agriculture. The application of nanoparticles as nanofertilizers and biostimulants can help improve growth and crop productivity, and it has therefore been mentioned as an essential tool to control the adverse effects of abiotic stress. However, nanoparticles have also been noted for their exceptional antimicrobial properties. Therefore, this work reviews the state of the art of different nanoparticles that have shown the capacity to control biotic stress in plants. In this regard, metal and metal oxide nanoparticles, polymeric nanoparticles, and others, such as silica nanoparticles, have been described. Moreover, uptake and translocation are covered. Finally, future remarks about the studies on nanoparticles and their beneficial role in biotic stress management are made.